Optimal Production Planning for PCB Assembly - Ho, William; Ji, Ping.; SpringerLink (Online service) (London : Springer London, 2007)
It is indisputable that printed circuit boards (PCBs) play a vital role in our daily life. With the ever-increasing applications of PCBs, one of the crucial ways to increase a PCB company$1 (Bs competitiveness in terms of operation efficiency is to minimize the production time so that the products can be introduced to the market sooner. Optimal Production Planning for PCB Assembly is the first book to focus on the optimization of the PCB assembly line$1 (Bs efficiency. This is done by: integrating the component sequencing and the feeder arrangement problems together for both the pick-and-place machine and the chip shooter machine; constructing mathematical models and developing an efficient and effective heuristic solution approach for the integrated problems for both types of placement machines, the line assignment problem, and the component allocation problem; developing a prototype of the PCB assembly planning system. The techniques proposed in Optimal Production Planning for PCB Assembly will enable process planners in the electronics manufacturing industry to improve the assembly line$1 (Bs efficiency in their companies. Graduate students in operations research will be familiar with the techniques and the applications of mathematical modeling after reading this advanced introduction to optimal production planning for PCB assembly. The Springer Series in Advanced Manufacturing publishes the best teaching and reference material to support students, educators and practitioners in manufacturing technology and management. This international series includes advanced textbooks, research monographs, edited works and conference proceedings covering all subjects in advanced manufacturing. The series focuses on new topics of interest, new treatments of more traditional areas and coverage of the applications of information and communication technology (ICT) in manufacturing.s
Optimization Techniques -- The Sequential Pick-and-Place (PAP) Machine -- The Concurrent Chip Shooter (CS) Machine -- The Line Assignment and the Component Allocation Problems -- A Prototype of the Printed Circuit Board Assembly Planning System (PCBAPS).
Keywords: Engineering; Mathematical models; Engineering design; Industrial engineering; Production engineering; Manufacturing industries; Machines; Tools; Electronics; Microelectronics; Electronic circuits; Engineering; Circuits and Systems; Industrial and Production Engineering; Manufacturing, Machines, Tools; Mathematical Modeling and Industrial Mathematics; Engineering Design; Electronics and Microelectronics, Instrumentation; Electronic books